EFFORTS TO IMPROVE TEACHERS' ABILITY IN IMPLEMENTING TEACHING LEARNING PROCESS THROUGH GROUP SUPERVISION AT SDN WIYUNG I/453 SURABAYA - Etiek Dyah Prasetyanti Haryono (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Supervision in education consists of administrative supervision and academic supervision. Academic supervision (instructional) is conducted by the supervisor or school principal, aimed at improving the quality of learning. Therefore, the assessment is more qualitative to improve the quality of learning. Administrative supervision is frequenty called as managerial supervision, aiming to identify the efficiency of the education system of each school in terms of learning services. Its assessment is quantitative because it involves the managerial level of the school as well as the elements of school resources. The implementation of academic supervision in every school is very important to do; that is an activity planned to provide assistance for teachers to improve the quality of learning. Supervisors or school principals may implement it through the support and assessment of learning processes in the classroom. Academic supervision contributes to the teacher's teaching performance so that the quality of learning produced is expected to increase.According to the description of School Action Research (PTS) and analysis of guidance results by streamlining Academic-based classroom supervision, it can be concluded that group supervision can improve the ability of teachers in implementing teaching and learning process at the school. The score of the Lesson Implementation Plan increased 27.9% from cycle I with average 3.4 to 4.4 in average in cycle II. The score of learning implementation appraisal increased 16.8% from cycle I with average 3.7 to average 4.3 in cycle II.